PENERAPAN MODEL PERMAINAN CIRCUIT TERHADAP PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK PADA SI SWA KELAS VII SMP NEGERI 2 ELLA HILIR - Jeki Jeki; Suyatmin Suyatmin; Indria Susilawati (STKIP Melawi, 2021)
Abstrack: This study aims to determine the effect of the circuit activity model of the game on squat style long jump learning in grade VII (seven) junior high school students Ella Hilir.This type of research is quasi-experimental with one group pretest posttest design. The method used in this research is the circuit activity model game method. The results of the pretest and posttest of t table have a significance value of 0.00 or smaller than 0.05 which means that there are differences in the learning of the basic technique of long jump squat style on students between before and after treatment. In the table one sample test looks average for before getting treatment = 57.91 and after getting treatment = 82.08. This means that the average value before receiving treatment is lower than after receiving treatment. With an inrease in the average value of = 24,17.Based on the results of the analysis shows that